2004
DOI: 10.1074/jbc.m404006200
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Mutagenesis of ω-Atracotoxin-Hv1a Reveals a Spatially Restricted Epitope That Confers Selective Activity against Insect Calcium Channels

Abstract: We constructed a complete panel of alanine mutants of the insect-specific calcium channel blocker -atracotoxin-Hv1a. Lethality assays using these mutant toxins identified three spatially contiguous residues, Pro 10 , Asn 27 , and Arg 35 , that are critical for insecticidal activity against flies (Musca domestica) and crickets (Acheta domestica). Competitive binding assays using radiolabeled -atracotoxin-Hv1a and neuronal membranes prepared from the heads of American cockroaches (Periplaneta americana) confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…Hv1a is a member of the -ACTX-1 family of 36-37 insecticidal residue peptides isolated from the Australian funnel web spider that block insect but not vertebrate, voltage-gated calcium channels ( [20] Fletcher et al, 1997). Previous alanine scanning mutagenesis studies by Tedford et al, [21] 2004 have identified 3 key functional residues (Pro10, Asn27, and Arg35) that determine specific binding to insect calcium channels. Here replacement of the 34th lysine residue in Hv1a with a glutamine residue by site directed mutagenesis was selected as glutamine is known to be present at this position of other members of the -ACTX-1 family ( [22] Tedford et al 2004) and was thus unlikely to disrupt biological function of the recombinant toxin.…”
Section: Analysis Of Biological Activity: Injection Bioassaysmentioning
confidence: 99%
“…Hv1a is a member of the -ACTX-1 family of 36-37 insecticidal residue peptides isolated from the Australian funnel web spider that block insect but not vertebrate, voltage-gated calcium channels ( [20] Fletcher et al, 1997). Previous alanine scanning mutagenesis studies by Tedford et al, [21] 2004 have identified 3 key functional residues (Pro10, Asn27, and Arg35) that determine specific binding to insect calcium channels. Here replacement of the 34th lysine residue in Hv1a with a glutamine residue by site directed mutagenesis was selected as glutamine is known to be present at this position of other members of the -ACTX-1 family ( [22] Tedford et al 2004) and was thus unlikely to disrupt biological function of the recombinant toxin.…”
Section: Analysis Of Biological Activity: Injection Bioassaysmentioning
confidence: 99%
“…The three disulfide bonds form an ICK motif in which the loop formed by the Cys11-Cys22 and Cys4-Cys18 SS bonds and the intervening sections of the peptide backbone is pierced by the Cys17-Cys37 SS bond ( Fig. 1.2B) (Tedford, 2001;Tedford et al, 2004a). The binding site of Hv1a on insect Ca v channels is not known but three residues on the toxin (Pro10, Asn27 and Arg35; see Fig.…”
Section: The Insecticidal Spider-venom Peptide ω-Hxtx-hv1amentioning
confidence: 99%
“…The binding site of Hv1a on insect Ca v channels is not known but three residues on the toxin (Pro10, Asn27 and Arg35; see Fig. 1.2C) mediate its interaction with Ca V channels (Tedford, 2001;Tedford et al, 2004a;King, 2007b;King et al, 2008).…”
Section: The Insecticidal Spider-venom Peptide ω-Hxtx-hv1amentioning
confidence: 99%
See 2 more Smart Citations